Rapid ice sheet response to deglacial and Holocene paleoenvironmental changes in eastern Prydz Bay, East Antarctica. (15th March 2022) - White, Duanne A.; Fink, David; Lilly, Kat; O'Brien, Phil; Dorschel, Boris; Berg, Sonja; Bennike, Ole; Gore, Damian B.; Fabel, Derek; Blaxell, Marcello; Jeromson, Matt; Codilean, Alexandru T.; et al.
Abstract: Prydz Bay lies at the terminus of one of East Antarctica's largest glacial systems and is a key region for understanding the response of the ice sheet to past and future environmental changes. In this study, we explore the dynamics and paleo-geometry of the ice sheet in eastern Prydz Bay, using a combination of bathymetric features on the seafloor to delineate past flow patterns, and cosmogenic nuclide dating of glacial deposits on land to constrain ice sheet terminus chronologies. Large streamlined bedforms on the sea floor record the existence of a primary ice stream in Svenner Channel, collecting ice from multiple tributary ice streams and discharging into the main trunk stream of the Lambert Glacier-Amery Ice Shelf system in Prydz Channel. The location and orientation of the north-eastern tributary to this ice stream also provide evidence for a substantial independent ice dome on the outer shelf at Four Ladies Bank. Exposure of ice-free areas at outer Rauer Group and Vestfold Hills indicates that grounding line retreat across eastern Prydz Bay was largely complete by ∼14 ka BP, and the ice margin had retreated to within ∼1 km of its present position by ∼10 ka BP. Onshore moraines record periods of ice margin retreat during the middle (∼6 ka BP) and very late (∼0.5 ka BP) Holocene coinciding with local warm periods. Subsidence recorded in modern Global Navigation Satellite System (GNSS) observations suggests the regional ice sheet was smaller than at present in the period between the middle and very late Holocene advances. The unusually dynamic ice sheet behaviour in this area is attributed to the smooth, reverse-slope bed characteristics of eastern Prydz Bay, which enabled rapid retreat of the ice sheet margin several hundred kilometres during deglacial events. Highlights: Post-LGM ice loss in Prydz Bay occurred earlier than other Antarctic sectors. Smooth, reverse slope bed in Prydz Bay drove rapid and dynamic deglaciation. Ice sheet readvance occurred in Prydz Bay during the late Holocene.